Recycling and reuse of treated wastewater in urban India: a proposed advisory and guidance document - World Bank; International Water Management Institute (International Water Management Institute, 2016)
Recycling and reuse of treated wastewater are an important part of the sanitation cycle and critical in an environment such as urban India with decreasing freshwater availability and increasing costs for delivering acceptable quality water, often from far distance. This report has been developed as a possible guidance document for the Indian government and gives substantial focus to the financial and economic benefits of wastewater recycling from the perspective of public spending. The report presents possible strategies for city and state planners and policymakers in view of the sanitation situation and the role of wastewater recycling in the larger cities in India (class I and II cities and towns with populations above 50,000), and focuses on recycling at the end of sewerage systems after treatment at sewage treatment plants.